Iloilo river history and ecology in a changing urban landscape - Funtecha, Henry F. (Danyag :the UPV journal of humanities and social sciences, 2009)
"Iloilo River is the life of Iloilo City even before the advent of the Spaniards. This role continued even until colonial times, especially with the opening of the Iloilo port to foreign trade in 1855 up to the rise and death of the "Queen City of the South". For centuries, Iloilo River has utilized as a source of food, as an artery of commerce and trade, as a place of livelihood and as a venue for leisure activities. Such activities have brought significant changes not only to the lives of the Ilonggos but also to the landscape along the banks of the river. However, Iloilo River that gave itself for the growth of Iloilo City is not fully appreciated by the people of Iloilo. They have ignored the well-being of the river for so many years. This attitude toward Iloilo River is greatly manifested by the present deplorable state or condition of the river. This paper describes the role of the Iloilo River in the development of the town of Iloilo into a city and ascertains the transformation in the river's physical environment from the opening of its port to foreign trade in 1855 up to the year 2000. It also determines the effects of such transformation on the river itself, particularly in its utility as a source of food and water, artery for commerce and trade, and place for bathing or leisure. The author utilized library resources in Iloilo and accounts written by Spaniards, and other foreigners who had visited Iloilo had been consulted for possible reference to the river. Local printed materials like the regional newspaper, Panay News, government records from the Department of Public Works and Highways, City Engineer's Office, City Planning Office, Department of Environment and Natural Resources, and the Philippine Ports Authority were also consulted. Informants consisted of local government officials, DENR personnel, and some owners of establishments along the Iloilo River, fishermen, and selected inhabitants from the communities along the riverbanks."